Front Cover Edisi 6 No 3 (Agustus 2022) - Rafian, Teguh (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2022)
Jurnal Riset dan Inovasi Peternakan(Journal of Research and Innovation of Animals) Chief EditorKusuma Adhianto Associate EditorDian SeptinovaRatna ErmawatiFitria Tsani FardaEtha ‘Azizah Hasiib Editorial BoardRudy SutrisnaFarida FathulAli HusniErwantoRr. RiyantiSyahrio TantaloKhaira NovaSri SuharyatiPurnama Edy Santosa SiswantoLimanTeguh Rafian